Controlled synthesis of ordered mesoporous g-C3N4 with a confined space effect on its photocatalytic activity. (May 2016) - Liu, Jinyuan; Yan, Jia; Ji, Haiyan; Xu, Yuanguo; Huang, Liying; Li, Yeping; Song, Yanhua; Zhang, Qi; Xu, Hui; Li, Huaming
Abstract: In this study, an ordered mesoporous g-C3 N4 (ompg-C3 N4 ) photocatalyst was synthesized successfully using silica material SBA-15 as the hard template via an impregnation method at different calcinations temperatures. The as-prepared samples were characterized by Brunauer–Emmett–Teller, Barrett–Joyner–Halenda, scanning electron microscopy, transmission electron microscopy, Fourier transform-infrared spectroscopy, wide and small angle X-ray diffraction, and UV–vis diffuse reflectance spectroscopy. The prepared materials were also evaluated to determine their photocatalytic degradation activities against methylene blue and rhodamine B under visible light irradiation. The calcination temperature greatly affected the structure and photocatalytic activity of ompg-C3 N4 . The sample calcined at 550 °C had the largest specific surface area and the highest photocatalytic activity, which were attributable to the characteristic confined space effect found in ordered mesoporous materials as well as the ordered mesoporous structure. A free radicals trapping test indicated that holes and ⋅ O 2 − were the main active species related to photocatalytic degradation.